The effect of feeding fermented distillers' grains diet on the intestinal metabolic profile of Guanling crossbred cattle - Luo, Xiaofen; Zhang, Tiantian; Xu, Duhan; Zhu, Mingming; Zhang, Junjie; Zhang, Rong; Hu, Qian; Wang, Yongxuan; He, Guangxia; Chen, Ze; Mei, Shihui; Zhou, Bijun; et al. (Frontiers in Veterinary Science, 2023)
To investigate effect of feeding fermented distiller's grains (FDG)-based diets on intestinal metabolites and related pathways in cattle, nine Guanling crossbred cattle (Guizhou Guanling Yellow cattle × Simmental cattle) were selected and randomly divided into a basal diet (BD) group and two experimental groups fed FDG replacing 15% and 30% of dietary concentrates (FDG-Case A and FDG-Case B) (n=3). Fresh jejunum (J) and cecum (C) tissues were collected for metabolomic analysis. Compared with the J-BD group, 30 and 100 differential metabolites (VIP > 1, p < 0.05) were obtained in the J-FDG-Case A group and J-FDG-Case B group, respectively, and the J-FDG-Case B vs J-FDG-Case A comparison revealed 63 significantly differential metabolites, which were mainly divided into super classes including Lipids and lipid-like molecules, Organoheterocyclic compounds, and Organic acids and derivatives. Compared with the C-BD, 3 and 26 differential metabolites (VIP > 1, p < 0.05) were found in the C-FDG-Case A group and C-FDG-Case B group, respectively, and C-FDG-Case B vs C-FDG-Case A comparison revealed 21 significantly different metabolites, which were also mainly divided into super classes including Lipids and lipid-like molecules, Organoheterocyclic compounds, and Organic acids and derivatives. A total of 40 metabolic pathways were